Adsorption/desorption of cationic dye on surfactant modified mesoporous carbon coated monolith: equilibrium, kinetic and thermodynamic studies - Malekbalaa, Mohamad Rasool (Elsevier, 2015)
Surfactant modified carbon coated monolith was used as an adsorbent for methylene blue (MB) adsorption. Effects of pH, salt, contact time, initial dye concentrations and temperature on dye adsorption were studied. Higher solution pH favoured MB adsorption. Furthermore, kinetics study showed that the adsorption could be better represented by the pseudo-second-order model. Linear and non-linear isotherm studies revealed better fitting of Langmuir model to adsorption data with maximum monolayer adsorption capacity 388 mg/g. The adsorption was found to be spontaneous and endothermic. Desorption studies indicate that 0.1 N HCl exhibits higher elution efficiency (82.1%) with appreciable quantitative MB recovery.